The Feminine Condition and Women's Sexual and Reproductive Health in Brazil and France - Silva, Simone Santana da; Fortuna, Cinira Magali; Monceau, Gilles; Soulière, Marguerite; Pilotti, Anne (Frontiers in Psychology, 2022)
Introduction: Elements mark the reality of the reading of the female body in symbolic constructions and social symbols in the exercise of their reproductive health. The study aims to identify elements that characterize the female condition while analyzing the reproductive health of Brazilian and French women. Materials and methods: A qualitative, multicenter, international study was conducted in Brazil and in France between 2016 and 2019. Data were produced through the use of semi-structured scripts. Focus groups and individual interviews were conducted with: women who gave birth, hetero-female couples who lived the experience of gestation and birth of a baby, as well as professionals of maternal and child care services or members of associations concerned with the health of mothers and babies. It was guided by the theoretical-methodological framework of Institutional Analysis, in the line of the French Institutional Socioclinics. Results: Sexual and reproductive health in the realities researched, in Brazil and France, are sometimes close, sometimes far apart. In what involves the Brazilian health system, abortion is criminalized and often performed illegally. Furthermore, pregnancy, childbirth and the postpartum are highly medicalized. In addition, childbirth is not assured as an experience for the woman and her family. This aspect is confirmed in the high numbers of cesarean sections performed or in maternal and infant mortality indicators. The French health system prioritizes vaginal deliveries, seems to assure more autonomy to women, but at the same time it is worn out by the logic of profit, efficiency of actions, and rationalization of practices. Associated to this, there are other intrinsic elements in the functioning of the institution that delineate the format of each country: notion of women's rights, violence against women, discussion regarding the oppression markers of race, gender, sexuality, and social class. Conclusions: In both countries, aspects about the social role of women's bodies, the established logics that are reflected in the decision to have children and in motherhood, the autonomy of women over their own bodies, the central values linked to the interruption of pregnancy, and the professional practices used in prenatal, delivery, and postpartum care.